THE ROLE OF EDUCATORS IN IMPROVING THE NUTRITIONAL KNOWLEDGE OF EARLY CHILDHOOD AT TK MUSLIMAT NU PAMEKASAN - Rey, Pinka Adebela; Prastyo,,, Danang (Al Hikmah Indonesian Journal of Early Childhood Islamic Education, 2024)
Early childhood nutrition education is essential to support their optimal growth and development. Good nutrition knowledge in children can prevent various health problems such as stunting and obesity. However, despite the abundance of literature emphasizing the importance of nutrition education in children, practices on the ground often do not align with theory, especially at the early childhood education level. Many children are still exposed to unhealthy eating habits due to a lack of understanding about nutrition. This study aims to identify the role of educators in improving early childhood nutrition knowledge at Muslimat NU Pamekasan Kindergarten. The method used was a descriptive qualitative approach with in-depth interviews with educators, parents, and school managers, as well as observation of activities at school. The main findings of this study show that educators have an important role in introducing the concept of balanced nutrition through activities such as eating together, providing nutritious food, and nutrition counseling. However, challenges such as low parental awareness, limited economic conditions, and unhealthy snacking habits outside of school are inhibiting factors. Improving children's nutritional knowledge requires collaboration between educators, parents and the surrounding environment to create a sustainable healthy lifestyle